(untitled) (Communications in Computational Physics, 2020)
From a spectral method combined with a predictor-corrector scheme, we numerically study the behavior in time of solutions of the three-dimensional generalized Kadomtsev-Petviashvili equations. In a systematic way, the dispersion, the blowup in finite time, the solitonic behavior and the transverse instabilities are numerically inspected.